The Effect of Economic Conditions and Parental Motivation on Student Achievement - Wulan Dewi Kurniawati; Suwahno Suwahno (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study was to determine whether there is a significant influence between economic conditions and parents' motivation on the learning achievement of fourth grade students at SDN Banyubiru 04. Methodology: Researchers used a quantitative approach with a correlation research design, the research subjects were 30 respondents. Data collection used a questionnaire instrument to obtain data on economic conditions and parents' motivation, learning achievement data was obtained through a document of first semester test report cards Main Findings: Based on the results of observations and discussion, it was found that: (1) The economic condition of the parents of grade IV students at SDN Banyubiru 04 was classified as high 46.66% by 7 respondents. (2) The motivation of parents of fourth grade students at SDN Banyubiru 04 is low, 40%, with 6 respondents. (3) The learning achievement of class IV students at SDN Banyubiru 04 is low at 53.33% for 8 respondents. There is a positive influence so that there is a correlation between economic conditions and parental motivation on student achievement in class IV SDN Banyubiru 04. Novelty/Originality of this study: the researcher recommends for further research in order to be able to conduct similar research with different and varied variables